Overweight and obesity among adult : a study at rural community in kampong Panagatan Ulu Keningau, Sabah - Rugaya @ Rugayah, binti Ibrahim (Faculty of Medicine & Health Sciences, 2008)
Obesity has reached epidemic proportions globally and it is a majo contributor of the global burden of chronic disease disease and disability, for example more than 1 billion adults overweight and at least 300 million of them clinically obese (WHO, 2003). Therefore, a descriptive cross-sectional study on overweight and obesity among adult age 21 to 64 years old was carried out a rural community in Kampung Panagatan Ulu Keningau, Sabah from 20th December 2008 to 02nd of January 2008.